Consequences of future climate policy: Regional economies, financial markets, and the direction of innovation - Marie-Theres von Schickfus (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2021)
With the Paris Agreement of 2016, 189 nations signed a legally binding document to keep global warming below 2 C, and to pursue efforts to limit the temperature increase to 1.5 C. It was recognized that this would reduce climate change impacts substantially. All signatories submitted "Intended Nationally Determined Contributions" (INDCs) where they specified their national emission reduction goals and pathways to achieve them. However, the INDCs submitted for the Paris Agreement "imply a median warming of 2.6-3.1 degrees Celsius by 2100" (Rogelj et al. 2016). A temperature increase by 2 C would already carry a very high risk for systems such as the Arctic sea ice and coral reefs. For a warming of 3 C above pre-industrial levels though, we are expected to face extensive losses of biodiversity and ecosystems; accelerated economic damages; and a high risk for abrupt and irreversible changes ("tipping points"), such as the melting of the Greenland ice sheet and the accompanying sea level rise (IPCC 2014b).
Keywords: C67; G14; G23; O34; Q35; Q38; Q43; Q55; R15; 330; Stranded assets; climate policy; expectations; utilities; event study; green innovation; patents; panel analysis; green finance; climate risk; intangible assets; institutional investors; renewable energy; crowding-out; regional economics; input-output ana